1993
DOI: 10.1037/h0079479
|View full text |Cite
|
Sign up to set email alerts
|

Institutional racism: An analysis of the mental health system.

Abstract: Institutional racism is defined and its conceptual application to the institution of psychiatry and the mental health system is described. Data on changes in the patient population and the provision and utilization of mental health services since deinstitutionalization are examined. Mental health policy and diagnostic and treatment issues are identified as areas in which institutional racism affects minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Institutionalized racism is “the extent to which racism is embedded in the dominant organizations and power structure of society, resulting in distinctive patterns of social disadvantage” (Wade, 1993, p. 543). Institutionalized racism has had its largest impact through economic exclusion and marginalization, such that racial stratification maps onto socioeconomic stratification (Harrison-Hale, McLoyd, & Smedley, 2004; Jones, 2000).…”
Section: Racial Discriminationmentioning
confidence: 99%
“…Institutionalized racism is “the extent to which racism is embedded in the dominant organizations and power structure of society, resulting in distinctive patterns of social disadvantage” (Wade, 1993, p. 543). Institutionalized racism has had its largest impact through economic exclusion and marginalization, such that racial stratification maps onto socioeconomic stratification (Harrison-Hale, McLoyd, & Smedley, 2004; Jones, 2000).…”
Section: Racial Discriminationmentioning
confidence: 99%
“…Attitudes toward masculinity and women and domestic violence also vary from culture to culture (Vandello & Cohen, 2003). Further, many men of color also have poor experiences in the mental health system (Wade, 1993). They may be overdiagnosed with some pathology (e.g., antisocial personality) while underdiagnosed for others (e.g., adjustment disorders) (Wade, 1993;White & Cones, 1999).…”
Section: Men Of Colormentioning
confidence: 99%
“…Flaherty and Meagher (1980) found that among black and white male schizophrenic inpatients who had similar global pathology ratings, ''black patients spent less time in the hospital, obtained lower privilege levels, were given more p.r.n. Similar studies have emphasized disparities between racial groups in terms of hospitalization rates, with blacks consistently overrepresented and other minority groups (Hispanics, Asian Americans/ Pacific Islanders, Native Americans) consistently underrepresented (Fernando, 1988;Lindsey & Paul, 1989;Snowden & Cheung, 1990;Wade, 1993). Seclusion and restraints were more likely to be used with black patients' ' (p. 679).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Based on these findings, the authors concluded that racial bias played a role in the psychiatric services provided to black patients as compared with whites. Similar studies have emphasized disparities between racial groups in terms of hospitalization rates, with blacks consistently overrepresented and other minority groups (Hispanics, Asian Americans/ Pacific Islanders, Native Americans) consistently underrepresented (Fernando, 1988;Lindsey & Paul, 1989;Snowden & Cheung, 1990;Wade, 1993). While avoiding cause-and-effect conclusions, most scholars cited racial bias as a critical intervening variable underpinning these disparities.…”
Section: Literature Reviewmentioning
confidence: 99%